Understanding Teachers’ OCB Beyond Religious Commitment - Desi Puspitosari; Sri Setyaningsih; Lina Novita (Cita konsultindo, 2026)
This study examines teachers’ Organizational Citizenship Behavior (OCB) beyond religious commitment among civil servant teachers in State Islamic Junior High Schools (MTsN) in West, East, and South Jakarta. OCB is conceptualized as discretionary behavior that goes beyond formal job requirements and contributes to school effectiveness and sustainability. The study aims to analyze the extent to which religious commitment influences teachers’ OCB and to identify the role of other organizational factors, particularly helping behavior, transformational leadership, and work motivation. A mixed-methods approach with a sequential exploratory design was employed using the Modeling and Optimization of Human Resource Strengthening (POP-SDM) framework. The qualitative phase involved in-depth interviews, while the quantitative phase included 220 civil servant teachers and was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that religious commitment has a positive effect on teachers’ OCB but does not serve as the dominant predictor. Transformational leadership emerged as the most influential determinant of OCB, followed by work motivation and helping behavior. These results indicate that teachers’ extra-role behavior in public Islamic schools cannot be explained solely by personal religiosity, but rather requires supportive organizational and leadership contexts. This study contributes to organizational behavior theory by challenging the assumption that religiosity alone drives OCB in faith-based public institutions and offers practical implications for leadership development and human resource management in Islamic education.